STRATFORD TO BOLLYWOOD: A COMPARATIVE STUDY OF SHAKESPEAREAN PLAYS AND THEIR INDIAN CINEMATIC ADAPTATIONS - Jagtap, Trupti Vijay; Kendre, Marot (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The plays of William Shakespeare have cut across geographical and cultural boundaries and come out as a major catalyst to literary and film adaptation all over the world. This research work is called Stratford to Bollywood A Comparative Study of Shakespearean Plays and their Indian Cinematic Adaptations, in which the researcher analyzes the manner in which certain Shakespearean tragedy and comedy plays were re-interpreted in the context of Indian cinema. Using a qualitative comparative method, the study examines such important adaptations as Haider (Hamlet), Maqbool (Macbeth), Omkara (Othello), Angoor (The Comedy of Errors), and Ram-Leela (Romeo and Juliet). The paper aims at analyzing the structural content of narration, the change in theme, characterization and re-contextualizing culture in order to comprehend the dynamics of adaptation. The results indicate that the main themes of Shakespeare like love, ambition, jealousy, betrayal, and identity are carried over but their meanings have been heavily transformed to suit the Indian socio-cultural, political, and cinematographic settings. The examples of Bollywood adaptations show a change of the individual-focused tragedy to the one rooted in the collective and socio-political reality, that is, incorporating such factors as caste relationships, political struggle, and customs. Moreover, the study emphasizes the importance of cinematic features such as music, dance, and symbolism as very vital elements in improving emotive intensity and viewer involvement. This study, by bringing together classical literature and mass media, will add to the body of work on the study of adaptation and film studies, as well as cross-cultural literary studies, and will help us to understand the timeless appeal of Shakespeare in modern Indian society